2008
DOI: 10.1165/rcmb.2007-0192oc
|View full text |Cite
|
Sign up to set email alerts
|

High Vascular Pressure–Induced Lung Injury Requires P450 Epoxygenase–Dependent Activation of TRPV4

Abstract: High vascular pressure targets the lung septal network, causing acute lung injury. While calcium entry in septal endothelium has been implicated, the channel involved is not known. This study tested the hypothesis that the vanilloid transient receptor potential channel, TRPV4, is a critical participant in the permeability response to high vascular pressure. Isolated lungs from TRPV4 1/1 or TRPV4 2/2 mice were studied at baseline or during high pressure challenge. Permeability was assessed via the filtration co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
137
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(145 citation statements)
references
References 36 publications
6
137
1
1
Order By: Relevance
“…The role of TRPV4 in lung injury has been studied previously in animal models in which injury was induced by mechanical stress or pressure, including a ventilator-induced lung injury model, a model of heart failure induced by aortic banding, and a model of myocardial infarction induced by arterial ligation (17,21,33). Ventilator-induced lung injury is associated with subsequent inflammation driven by macrophages, and it was suggested that macrophage-expressed TRPV4 channels play a crucial role in activating these cells (16).…”
Section: Discussionmentioning
confidence: 99%
“…The role of TRPV4 in lung injury has been studied previously in animal models in which injury was induced by mechanical stress or pressure, including a ventilator-induced lung injury model, a model of heart failure induced by aortic banding, and a model of myocardial infarction induced by arterial ligation (17,21,33). Ventilator-induced lung injury is associated with subsequent inflammation driven by macrophages, and it was suggested that macrophage-expressed TRPV4 channels play a crucial role in activating these cells (16).…”
Section: Discussionmentioning
confidence: 99%
“…The observation that L-NAME converted the pulmonary vasodilator response to GSK1016790A to a biphasic response with a potent pulmonary vasoconstrictor component may suggest that in pathophysiological conditions characterized by increased oxidative stress, which can inactivate NO, TRPV4 channel activation could increase hydrostatic pressure in the lung and enhance edema formation (24). It has been suggested that TRPV4 channel activation plays a role in pulmonary edema induced by elevated pulmonary venous pressure (2,8,26). It has been reported that TRPV4 receptor blockade prevented the increase in lung permeability and pulmonary edema associated with increased pulmonary venous pressure (18).…”
Section: Discussionmentioning
confidence: 99%
“…Our experiments rule out downregulation of eNOS or lack of eNOS substrate which have been shown to underlie endothelial dysfunction in pulmonary arterial hypertension, 31,32 and consequently suggest that lung endothelial dysfunction in CHF may be attributable to impaired posttranslational regulation of eNOS. 17,22 failed to elicit a [Ca 2ϩ ] i increase in CHF lungs. TRPV4 and TRPV2 were both downregulated in CHF, seemingly supporting the notion that downregulation of these cation channels may underlie the loss of endothelial mechanosensitivity.…”
Section: Lung Endothelial Dysfunction In Chfmentioning
confidence: 91%